HOTAIR Promotes Proliferation, Migration, and Invasion of Ovarian Cancer SKOV3 Cells Through Regulating PIK3R3 - Dong, Lijun (Med Sci Monit, 2016)
BACKGROUND: The aim of this study was to determine the effect on proliferation, migration, and invasion after silencing HOTAIR in ovarian cancer SKOV3 cells, and to elucidate the potential mechanism. MATERIAL/METHODS: We analyzed the mRNA expression level of HOTAIR and PIK3R3 in ovarian cancer SKOV3, OVCAR3, and A2780 cell lines. We analyzed the mRNA expression level of HOTAIR and PIK3R3 in ovarian SKOV3 after transection with miR-214 or miR-217. We analyzed the mRNA and protein expression level of PIK3R3 when silencing HOTAIR. We analyzed the expression of HOTAIR when silencing PIK3R3. We analyzed the proliferation, migration and invasion in ovarian cancer SKOV3 after silencing HOTAIR or PIK3R3. RESULTS: The expression of HOTAIR and PIK3R3 in ovarian SKOV3 and OVCAR3 was increased compared with A2780 cells (P<0.05). The mRNA level of HOTAIR and PIK3R3 in ovarian cancer SKOV3 cells was decreased when transected with miR-214 or miR-217 compared to negative control (p<0.05). The mRNA and protein level of PIK3R3 was decreased when HOTAIR was silenced and the mRNA level of HOTAIR was decreased when PIK3R3 was silenced (p<0.05). The proliferation, migration and invasion was decreased in ovarian SKOV3 when HOTAIR or PIK3R3 was silenced (p<0.05). CONCLUSIONS: HOTAIR can promote proliferation, migration, and invasion in ovarian SKOV3 cells as a competing endogenous RNA.